Reliability analysis for socio-technical system, case propene pumping. (October 2015) - Ávila, S.F.
Highlights: Some socio-economic and environmental challenges be incorporated in the Industrial Sector in 2020. The greater integration between teams facilitates standardization of routines. The reliability is not an isolated study for each functional part of the industry. The cause of failure in complex systems depends of the worker, machine, and the process. Abstract: Reliability is not a specified study for each functional part of the industry, isolated one from other. The reliability of each part is interconnected with each other and their level of integration depends on the level of automation, type of process, management style, and organizational environment. By understanding on relations between the functions of these systems becomes possible to study the integrated reliability. This knowledge allows the formatting of factors that increase the performance of staff and of equipment leading to greater organizational efficiency. This work aims to clarify how the different reliabilities communicate with each other, and how to establish integrated programs without excessive resources for deployment and management of integrated reliability. A new management type and organizational environments are proposed to transform people and equipment even more reliable to the system. In this moment we are proposing new techniques to analyze the failure, the accident, the task, and the hazards. The task analysis allows the integration between the operation and the worker that, in consequence, becoming more reliable. The design of process control allows maintenance of process capability in response to operational actions. The reliability and the maintainability of equipment depend on the level of automation and confidence in the project work. A good tool to interface man–machine integrates the human and the equipment, increasing the reliability system. The skills to perform a well-designed task (operational reliability) keep the equipment under control. The knowledge of the operator ensures that processes are been controlled and are able to meet their goals. The success of integration of the reliabilities is ensured and achieved with the adoption of new organizational patterns and new management styles. Thus it becomes possible to transform policy into practice without having divergent values or reduce conflict between priorities in the areas of safety and production.